Gender Inequality in COVID-19 Times: Evidence from UK Prolific Participants - Sonia Oreffice; Climent Quintana-Domeque (Institute of Labor Economics (IZA), 2020)
We investigate gender differences across socioeconomic and wellbeing dimensions after three months of lockdown in the UK, using an online sample of approximately 1,500 respondents in Prolific, representative of the UK population with regards to age, sex and ethnicity. We find that women's mental health is worse than men's along the four metrics we collected data on, that women are more concerned about getting and spreading the virus, and that women perceive the virus as more prevalent and lethal than men do. Women are also more likely to expect a new lockdown or virus outbreak by the end of 2020, and are more pessimistic about the current and future state of the UK economy, as measured by their forecasted present and future unemployment rates. Consistent with their more pessimistic views about the economy, women choose to donate more to food banks. Women are more likely to have lost their job because of the pandemic, and working women are more likely to hold more coronavirus-risky jobs than men. We also find that between February and June 2020 women have decreased their work hours, but increased housework and childcare much more than men. These gender inequalities are not driven by differences in age, ethnicity, education, family structure, income in 2019, current employment status, place of residence or living in rural/urban areas.
Keywords: H1; J1; J16; 330; Coronavirus; sex; inequity; wellbeing; health; employment; perceptions; donations; COVID-19